2020
DOI: 10.1111/bph.15287
|View full text |Cite
|
Sign up to set email alerts
|

Small intestinal glucose and sodium absorption through calcium‐induced calcium release and store‐operated Ca2+ entry mechanisms

Abstract: Background and Purpose: Luminal glucose enhances intestinal Ca 2+ absorption through apical Ca v 1.3 channels necessary for GLUT2-mediated glucose absorption. As these reciprocal mechanisms are not well understood, we investigated the regulatory mechanisms of intestinal [Ca 2+ ] cyt and SGLT1-mediated Na +-glucose co-transports. Experimental Approach: Glucose absorption and channel expression were examined in mouse upper jejunal epithelium using an Ussing chamber, immunocytochemistry and Ca 2+ and Na + imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 44 publications
(76 reference statements)
1
19
0
Order By: Relevance
“…Our former studies, including T29 (Yang et al, 2018) and SCBN (Zhang et al, 2019;Zhang et al, 2021), confirmed that SOCE/ORAC mechanism is in IECs through SOCE blockers or knockdown cells. IEC-6 cells are usually applied as an IEC model to study intestine epithelial anion secretion (Wenzl et al, 1989), which has also been certificated the participation of SOCE mechanism (Chung et al, 2015).…”
Section: Luminal Carbachol Induced Ca 2+ -Dependent Duodenal I Sc Through Serosal Ca 2+ Entrysupporting
confidence: 60%
See 1 more Smart Citation
“…Our former studies, including T29 (Yang et al, 2018) and SCBN (Zhang et al, 2019;Zhang et al, 2021), confirmed that SOCE/ORAC mechanism is in IECs through SOCE blockers or knockdown cells. IEC-6 cells are usually applied as an IEC model to study intestine epithelial anion secretion (Wenzl et al, 1989), which has also been certificated the participation of SOCE mechanism (Chung et al, 2015).…”
Section: Luminal Carbachol Induced Ca 2+ -Dependent Duodenal I Sc Through Serosal Ca 2+ Entrysupporting
confidence: 60%
“…We previously demonstrated that carbachol (CCh), a stable chemical analog of neurotransmitter ACh, triggered IP 3 R/ER Ca 2+ release, but caffeine triggered RyR/ER Ca 2+ release, both of which stimulated serosal store-operated Ca 2+ entry (SOCE) mechanism and eventually induced Ca 2+ -dependent duodenal anion secretion (Yang et al, 2018;Zhang et al, 2019;Zhang et al, 2021) However, it is currently unclear: 1) whether [Ca 2+ ] cyt is also a critical cell signaling for other most common and important secretagogues, such as PGE 2 and 5-HT; 2) if serosal SOCE is a universal mechanism for Ca 2+dependent duodenal anion secretion; 3) if so, what molecular components of the SOCE are involved in this process; and 4) if CCh evokes a Ca 2+ -dependent anion secretion when applied from the mucosal side of the duodenum, although it is well known to stimulate it from the serosal side. Therefore, we aimed to investigate these important issues using native duodenal epithelial tissues in mice as a follow-up study.…”
Section: Introductionmentioning
confidence: 99%
“…As male DKO mice appeared to have a decreased ability to absorb glucose given orally, we next turned to the small intestine for analysis, considering its role in glucose transport and metabolism [ [31] , [32] , [33] ]. Histologic evaluation of the jejunum of the DKO mice that underwent metabolic phenotyping did not reveal any abnormalities ( Figure 6 A), and neither villi length in the jejunum nor total small intestine length was different between control and DKO mice ( Figure 6 B).…”
Section: Resultsmentioning
confidence: 99%
“…As an important second messenger, Ca 2+ is involved in various physiological processes, such as muscle contraction, hormone secretion, and neurotransmitter release. We have previously reported Ca 2+ signaling regulation of ion secretion and absorption through SGLT1 in the intestinal epithelium ( Zhang F. et al, 2019 ; Yinghui et al, 2021 , Zhang et al, 2021 ). We also revealed that Ca 2+ signaling regulates H + /peptide transporter PEPT1 to mediate intestinal Gly-Sar uptake in mice ( Xu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Serosal SOCE Mechanism in Ca 2+ -Mediated Gln-I sc Since the store-operated Ca 2+ entry (SOCE) is a well-established mechanism to regulate the Ca 2+ -dependent functions in IEC, including jejunal glucose absorption (Zhang et al, 2021),we examined whether the SOCE mechanism regulates ileal Gln-I sc and started with GdCl 3 , a commonly used SOCE blocker (Zhu et al, 2020). As shown in Figure 6A, serosal addition but not mucosal addition of GdCl 3 (30 µM) inhibited Gln-induced I sc , consistently with the previous finding of the serosal localization of the SOCE (Zhang et al, 2021). Secondly, serosal application of YM-58483 (0.3 µM) and GSK-7975A (100 µM), two selective SOCE blockers with different structures, also reduced Gln-I sc (Figures 6B,C).…”
mentioning
confidence: 99%